2019
DOI: 10.1044/2019_ajslp-18-0160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age at Cochlear Implantation on Learning and Cognition: A Critical Assessment

Abstract: Purpose Age at cochlear implantation frequently is assumed to be a key predictor of pediatric implantation benefits, but outcomes related to learning and cognition appear inconsistent. This critical assessment examines relevant literature in an effort to evaluate the impact of age at implantation in those domains for individuals who received their devices as children. Method We examined 44 peer-reviewed articles from 2003 to 2018 considering age at impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…This result suggests that since the difference in performance is greater in younger children (7-year-olds), it seems to decrease as age increases. A possible explanation for this result is the major exposure, in terms of time, to the auditory stimuli experienced by older children (see Duchesne and Marschark, 2019;Marschark et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that since the difference in performance is greater in younger children (7-year-olds), it seems to decrease as age increases. A possible explanation for this result is the major exposure, in terms of time, to the auditory stimuli experienced by older children (see Duchesne and Marschark, 2019;Marschark et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of academic achievement among CI users have demonstrated significant benefits among primary school-aged children, but those benefits consistently have been found attenuated or absent among CI users in secondary and postsecondary education Convertino et al [4,10,12,13,24,26]. Among those studies that included consideration of age of implantation Crowe et al [12,13,24] none found significant effects of age of implantation among older CI users Marschark et al [15]. Tests typically used in such studies assess current abilities in targeted domains such as reading or mathematics.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…That is, although deaf children immersed early on in sign language environments have been found to demonstrate better reading achievement during the primary school years relative to deaf children who are not, the benefits of early sign language appear to be reduced or absent by high school and college age. Crowe et al [5,14,15,24,[26][27][28][29], suggested several possible explanations for such findings. Specifically, with regard to CI users, Archbold [5] noted that the materials and goals of reading at the secondary school level are very different than those at the primary school level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current research on deaf children who use CIs has extended beyond functional communication, as improved language acquisition can also affect social development and ToM abilities [65]. In order to fully understand the relationship between cochlear implantation and ToM, different types of predictors should be included in the studies: age at implantation, level of specific language abilities, and family factors, including the quality of parental conversational input and the parents' perceptions of their child's social functioning.…”
Section: Language and Conversation In Deaf Children With Cismentioning
confidence: 99%